KEBERADAAN PROFITABILITAS, BIAYA OPERASIONAL DAN LEVERAGE TERHADAP PAJAK PENGHASILAN BADAN PADA PERUSAHAAN PUBLIK SEKTOR KESEHATAN - Merry Kalventri; Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Tax is the largest income for the state. For companies, taxes are a burden that will reduce profits. Therefore, companies try to take advantage of taxes through various ways, such as using debt and maximizing operational costs. This study aims to analyze the effect on profitability, operating costs, and corporate income tax leverage. The object of research is a company that is included in the health sector based on the Indonesian Stock Exchange Industry Classification which is listed on the Indonesia Stock Exchange during 2018-2020. Sampling using non-probability sampling technique with purposive sampling technique. The results showed that the data passed the coefficient similarity test and the classical assumption test. The variation of the dependent variable is explained by the independent variable of 82.5%. The variables of profitability, operating costs and leverage simultaneously have an effect on corporate income tax. In the t-test, profitability and operating costs of Sig 0.000 mean that the second variable has a significant effect on corporate income tax. While decent leverage Sig 0.734 means that there is no evidence that leverage has a significant effect on corporate income tax. The conclusion of this study is profitability and operating costs have a positive and significant effect on corporate income tax. Meanwhile, there is no evidence that leverage has a positive and significant effect on corporate income tax.